HIPERURISEMIA DAN RESPONS IMUN - Manampiring, Aaltje E. (UNIVERSITAS SAM RATULANGI, 2011)
Abstract: Hyperuricemia, a highly prevalent condition in adult population, is associated with hemodynamic and metabolic disturbances. Albeit, pathophysiological aspects of hyperuricemia are still not clearly understood. Uric acid plays an essential role in immunity by induction of some cytokines and chemokines, such as TNFÎ±, Il-1Î², IL-6, CXCL8 (IL-8), and CXCL1 (growth-related oncogene Î±). Deposits of monosodium urate crystals in joint cavities and periarticular tissuesÂ are related to an autoinflammatory disturbance, namely gout. Keywords: hyperuricemia, monosodium urate crystal, immune responsse.Â Â Abstrak: Hiperurisemia merupakan suatu keadaan yang umum dijumpai pada populasi dewasa dan berhubungan dengan kelainan metabolik dan hemodinamik. Aspek patofisiologik dari hiperurisemia belum sepenuhnya dipahami dengan jelas. Asam urat berperan penting dalam imunitas dengan menginduksi berbagai sitokin dan kemokin, antara lain TNFÎ±, Il-1Î², IL-6, CXCL8 (IL-8) dan CXCL1 (growth-related oncogene Î±). Deposit kristal monosodium urat di dalam rongga sendi dan jaringan periartikuler berkaitan dengan gangguan autoinflamasi yang dikenal sebagai gout. Kata kunci: hiperurisemia, kristal monosodium urat, respons imun.